2004
DOI: 10.1023/b:pham.0000041457.64638.8d
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of the HIV-1 Protease Inhibitor Lopinavir (ABT-378) Given in Combination with Ritonavir in Rats, Dogs, and Humans

Abstract: Lopinavir was subject to extensive metabolism in vivo. Co-administered ritonavir markedly enhanced the pharmacokinetics of lopinavir-derived radioactivity in rats, probably due to inhibition of presystemic and systemic metabolism, leading to an increased exposure to this potent HIV protease inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 18 publications
7
102
0
Order By: Relevance
“…When expressed as percentages of total serum LPV concentrations, 1.6 Ϯ 0.8% of the drug was unbound in the GDM group compared with 0.6 Ϯ 0.3 and 0.6 Ϯ 0.4% in the vehicle and insulin-treated groups, respectively ( p Ͻ 0.05). LPV plasma protein binding in the rat has been shown to be constant across a range of total LPV concentrations that encompasses all of the values observed in our study (Kumar et al, 2004).…”
Section: Lopinavir Exposure In a Rat Model Of Gestational Diabetessupporting
confidence: 70%
See 1 more Smart Citation
“…When expressed as percentages of total serum LPV concentrations, 1.6 Ϯ 0.8% of the drug was unbound in the GDM group compared with 0.6 Ϯ 0.3 and 0.6 Ϯ 0.4% in the vehicle and insulin-treated groups, respectively ( p Ͻ 0.05). LPV plasma protein binding in the rat has been shown to be constant across a range of total LPV concentrations that encompasses all of the values observed in our study (Kumar et al, 2004).…”
Section: Lopinavir Exposure In a Rat Model Of Gestational Diabetessupporting
confidence: 70%
“…In a study of LPV metabolism and disposition in the rat, 69.5% of an intravenous LPV dose was recovered in bile after 24 h and approximately 86% of this occurred in the first 2 h (Kumar et al, 2004). In maternal liver, at 45 and 60 min, LPV concentrations in GDM were less than one third of control values.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy volunteers (n ϭ 16; 6 female, 3 Hispanic, and 2 black individuals) were administered 400-mg-100-mg lopinavir-ritonavir tablets twice daily to steady state, and on the morning of pharmacokinetic sampling, drug intake was observed directly and timed. The evening dose was omitted, and blood was drawn predose (0 h) and at 0.5, 1, 2, 3, 4,6,8,10,12,16,20,24,30,36,48,60, and 72 h postdose. Plasma lopinavir and ritonavir concentrations were quantified by a fully validated high-performance liquid chromatography-tandem mass spectrometry method (6), with lower limits of quantification (LLQs) of 0.005 and 0.002 mg/liter for lopinavir and ritonavir, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Due to limited oral bioavailability and poor pharmacokinetics of many of the currently available PIs, additional efforts have been made to design more potent PIs with improved pharmacokinetic properties. Lopinavir (LVR), an analog of ritonavir (RVR) is a potent inhibitor of wild type and mutant HIV protease (Ki =1.3-28 pM) (Kumar et al, 2004). Its structure is outlined in Fig.1.…”
Section: Introductionmentioning
confidence: 99%
“…The low oral bioavailability of LVR was attributed to high first-pass metabolism (Kumar et al, 2004). In vitro investigations with human liver microsomes have shown that cytochrome P450 3A plays a predominant role in the metabolism of LVR.…”
Section: Introductionmentioning
confidence: 99%